Phytochemical profile of genotypes of Euterpe edulis Martius – Juçara palm fruits. (February 2019) - Barroso, Maria E.S.; Oliveira, Bruno G.; Pimentel, Elisângela F.; Pereira, Pedro M.; Ruas, Fabiana G.; Andrade, Tadeu U.; Lenz, Dominik; Scherer, Rodrigo; Fronza, Marcio; Ventura, José A.; Vaz, Boniek G.; Kondratyuk, Tamara P.; et al.
Abstract: Juçara fruit ( Euterpe edulis ) has received attention due to its similarities to Euterpe oleracea (Açaí). The aim of this study was to evaluate the cytotoxicity, bioactive compounds, antioxidant capacities and chemopreventive activities of the fruit pulps of six populations of E. edulis (J1-J6) and one population of E. espiritosantense from different ecological regions. ESI(−)-FT-ICR-MS was used to evaluate the pulp composition. The varieties J1 and J4 presented higher polyphenol contents, while J2 and J5 showed higher anthocyanin contents. ESI-FT-ICR MS identified cyanidin-3-rutinoside (J1, J2, J3, J4, J5, J7), protocatechuic acid, methylhydroxybenzoate hexoside and rutin (J1 to J7) and malvidin-glicoside (J2 to J5). The J2, J3, J4, J5 and J6 samples inhibited inducible nitric oxide synthase (iNOS). The chemoprevention biomarker quinone reductase was significantly induced by J6. Pulp from plants J3, J4, J6 and J7 significantly reduced the inflammatory cytokine TNF-α, and J6 was selected as having the most potential for cultivation and consumption. Graphical abstract: Unlabelled Image Highlights: Euterpe edulis presented high antioxidant capacity. Juçara varieties were of good quality. E. edulis Juçara fruit (J6) is indicating for in natura consumption or for use as nutraceutical.